Monetary Policy Transmission in the Euro Area 2003
DOI: 10.1017/cbo9780511492372.026
|View full text |Cite
|
Sign up to set email alerts
|

The bank-lending channel of monetary policy: identification and estimation using Portuguese micro bank data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 209 publications
4
22
0
2
Order By: Relevance
“…The main empirical evidence for the evidence of Islamic financing channel is shown by the positive coefficient on the variable LIQ (Bernanke and Blinder, 1988;Bernanke and Gertler, 1995;Farinha and Carlos, 2001). This is because a lot of obtained bank liquidity from the deposit will affect the supply of loans to meet capital demand by economic sector for investment or consumption.…”
Section: Results Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main empirical evidence for the evidence of Islamic financing channel is shown by the positive coefficient on the variable LIQ (Bernanke and Blinder, 1988;Bernanke and Gertler, 1995;Farinha and Carlos, 2001). This is because a lot of obtained bank liquidity from the deposit will affect the supply of loans to meet capital demand by economic sector for investment or consumption.…”
Section: Results Of Analysismentioning
confidence: 99%
“…Among them are Altunbas, Fazylov and Molyneux (2002) and Pizarro-Barcelo (2009) in the European countries, Nertherlands (de Haan, 2001), Greece (Brissimis, Kamberoglu and Simigainnis, 2001), Portugal (Farinha and Carlos, 2001), Japan (Ogawa,2000), Italy (Gambacorta and Mistrulli,2004) and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Bank profitability and bank liquidity both appear negative and statistically insignificant. Farinha (2001) found that liquidity do not appear as relevant bank characteristics in determining a differential impact of monetary policy on the supply of bank loan. Credit risk appears negative and statistically significant.…”
Section: Regression Analysesmentioning
confidence: 93%
“…However, the sample was adjusted for mergers and acquisitions among banks by backward aggregation of the balance sheet items. Although this is the most commonly used approach in the literature (Ehrmann et al, 2001;Worms, 2001;Gambacorta, 2005;Farinha and Marques, 2003;De Haan, 2001;Havrylchyk andJurzyk, 2005 andPruteanu-Podpiera, 2007), this may bias the data because changes in the management of the merged bank and the know-how of the staff are not controlled for. After the adjustment of the sample for the mergers between two banks that occurred in 2001 and 2006 and two acquisitions in 2001 respectively, over the whole sample period we work with an unbalanced set of 20 banks.…”
Section: Data Issues and Summary Statisticsmentioning
confidence: 99%